PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS PENDEKATAN OPEN ENDED UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DAN BERPIKIR KREATIF SISWA KELAS VIII SMP BERASTAGI T.A. 2014/2015 - Arianti Evalida Br Karo; Hasratuddin . . (Universitas Negeri Medan, 2016)
ABSTRACTThe purpose of this study was to: (1) develop student worksheets based open ended approach to improve mathematical problem solving skills and creative thinking of students; (2) determine the effectiveness of student worksheets were developed based on open-ended approach to improve mathematical problem solving and creative thinking of students; and (2) determine students' response to student worksheet that was developed based on open-ended approach. Population in this research is class VIII SMP Negeri 3 Berastagi. This research is the development by using 4-D model of S. Thiagarajan which was limited to the define, design and the development phase without the disseminate phase. Techniques of data collection in this researchby using validation sheet of RPP (Lesson Plan), LKS (Student Worksheet), test and student questionnaire responses. The results showed that: (1) Produced student worksheets based open ended approach that category is valid with a percentage of 78.38%. (2) The effectiveness of student worksheet that was developed based on open-ended inferred based approaches that: (a) the classical completeness of 87,5%, and (b) achievement of specific learning objectives (TPK): complete. 3) The response of students to the student worksheets were developed based on open-ended approach is positive.Keywords : students worksheet, open ended, problem solving, creative thinking